72.2k views
3 votes
Is the rule ax+by=d the same as y=mx+b?

User Ggll
by
5.0k points

1 Answer

1 vote

No, they are not the same.

If you made y the subject for each of them:

ax + by = d

by = -ax + d

y = -(a/b)x + (d/b)

which may not be the same as

y = mx + b

since b is already a fixed variable.

But I'm not sure if your question is just asking about whether ax + by = d can be expressed as linear form. If it was asking that, then the working above shows that it can be expressed in linear form (y = mx + b)

User Lucasweb
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.